Analisis Politik dan Kebijakan Perguruan Tinggi Islam - Maryati, Maryati; Firdaus, Arif Fakih; Wahyudin, Agus Novi; Fauzi, Anis; Aminah, Neneng (LPPM Institut Pendidikan Nusantara Global, 2025)
Islamic universities in Indonesia face significant challenges in balancing Islamic values with the needs of modern education and global competition. The dynamics of changes in national higher education policies and the demands of international accreditation create adaptive pressure for these institutions to transform without losing their distinctive identity. This research aims to analyze the effectiveness of Islamic higher education policies in integrating Islamic values with international academic standards, as well as identifying optimal policy models for institutional development in the digital era. How can Islamic universities develop policies that strengthen Islamic identity while increasing global competitiveness? What are the challenges of implementing scientific integration policies in Islamic universities? The research used a qualitative approach with a case study method at five leading Islamic universities. Data were collected using library research method, by analyzing various sources from books and journals related to the theme of the mutual relationship between politics and policy and education in Islamic universities. The study identified three models of effective integration policies: (1) transformative-adaptive model, (2) conservative-selective model, and (3) progressive-innovative model. Policy implementation is influenced by leadership, organizational culture, and capacity factors. Universities that implement the transformative-adaptive model show an optimal balance between strengthening Islamic values ​​and increasing global competitiveness.